SENSORIMOTOR STIMULATION AFTER ANTERIOR CRUCIATE LIGAMENT RECONSTRUCTION - David Kantchev; Gergana Nenova; Mina Ivelinova; Nadya Manova; Konstantin Dobrev (Peytchinski Publishing, 2024)
Introduction: postural balance is a concept that refers to the body's ability to maintain its center of gravity while relying on a support area. Purpose: to develop and implement a combined physiotherapy programme with sensorimotor exercises and to monitor its effectiveness after anterior cruciate ligament reconstruction. Material and methods: Material: 15 men (mean age 25.16) were observed after anterior cruciate ligament reconstruction. They underwent a physiotherapy programme combined with additional exercises for sensorimotor stimulation. The sensorimotor stimulation exercises were specifically tailored to overcome muscle imbalance and pathological proprioceptive information from the operated knee joint. Methods: Functional methods include lower extremity centimetry, range of motion in the knee joint, manual muscle testing, static and dynamic balance tests, and postural control tests. Statistical methods: statistical data grouping; Cronbach's test; descriptive method; statistical hypotheses testing; correlation analysis. The data was processed with SPSS v.24.0 for Windows. Results: according to the literature, the main cause of impaired proprioception and mechanoreception is the loss of mechanoreceptive afferency due to tissue damage in the knee joint. This requires an income of sensory information from neighboring healthy structures. The inclusion of sensorimotor exercises helps build new motor skills, activity, and regulation that require peripheral stimuli. The results from the static and dynamic portions of the test show the possibility of restoring impaired sensorimotor information. Conclusion: the combination of classic physiotherapy and sensorimotor stimulation influences the support and motor function of the lower extremities.